Plant genetic manipulation for crop protection - Gatehouse, A. M. R.; Hilder, V. A.; Boulter, D. (Biotechnology in agriculture series, 1992)
A major goal in current plant biotechnology is the modification of plant genomes to produce crops with enhanced resistance to pests, pathogens and herbicides. This will permit crop protection with reduced levels of application of chemical insecticides and fungicides, and the more selective use of herbicides. This book reviews our current knowledge of this rapidly advancing field, including a review of the successful use of Bt.t genes and consideration of legislation and marketing. The book will be of great interest to plant biotechnologists, genetic engineers and workers in plant pathology or agricultural entomology wishing to keep abreast of the subject.